2011
DOI: 10.1002/nml.20051
|View full text |Cite
|
Sign up to set email alerts
|

Results from a strategic planning process: Benefits for a nonprofit organization

Abstract: A nonprofit professional organization in education undertook

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 9 publications
0
20
0
2
Order By: Relevance
“…Para isso, a organização é direcionada pelos gestores a utilizar ferramentas gerenciais como o Planejamento Estratégico. E, então, a realização e aplicação dessa estratégia é seguida por particularidades do setor, uma vez que a ferramenta tem uma perspectiva econômico-financeira (Ensslin & Vianna, 2007 A profissionalização de uma entidade sem fins lucrativos requer educação no Planejamento Estratégico, para que seja preparada para os desafios, refinando sua missão e obtendo retorno dos seus membros, para melhoria de desempenho, em busca da satisfação e atendimento das necessidades dos atendidos, fazendo assim a organização se move de forma mais assertiva e determinada (Mchantton, Bradshaw, Gallagher, & Reeves, 2011).…”
Section: Planejamento Estratégico No Terceiro Setorunclassified
“…Para isso, a organização é direcionada pelos gestores a utilizar ferramentas gerenciais como o Planejamento Estratégico. E, então, a realização e aplicação dessa estratégia é seguida por particularidades do setor, uma vez que a ferramenta tem uma perspectiva econômico-financeira (Ensslin & Vianna, 2007 A profissionalização de uma entidade sem fins lucrativos requer educação no Planejamento Estratégico, para que seja preparada para os desafios, refinando sua missão e obtendo retorno dos seus membros, para melhoria de desempenho, em busca da satisfação e atendimento das necessidades dos atendidos, fazendo assim a organização se move de forma mais assertiva e determinada (Mchantton, Bradshaw, Gallagher, & Reeves, 2011).…”
Section: Planejamento Estratégico No Terceiro Setorunclassified
“…In their investigation of nonprofit boards, O'Regan and Oster (2005) found more than 90% of the participating board members reported mission fulfillment was their primary motive for serving on the board of directors. While mission statements should indicate the unique purpose of a nonprofit organization, previous research indicates broad and vague statements among nonprofit mission statements (McHatton, Bradshaw, Gallagher, & Reeves, 2011). The lack of specific details suggests some nonprofits may have failed to realize they cannot solve all social issues on their own (Kaplan, 2001).…”
Section: Volunteer Motivesmentioning
confidence: 99%
“…However, mission statements can always be revised to better reflect the purpose of an organization. In their case study of the Council for Exceptional Children, McHatton et al (2011) reported how the organization revised its mission statement to better reflect its perceived values and goals through a strategic planning session based on inputs from key internal stakeholders. In their exploratory study of how leaders of nonprofit organizations in Pittsburgh evaluated funding sources, Kearns et al (2014) found the most common evaluation criteria were related to the mission of the organization.…”
Section: Volunteer Motivesmentioning
confidence: 99%
See 2 more Smart Citations